PENGARUH IKLIM ORGANISASI DAN PEMBERDAYAAN TERHADAP KEPUASAN KERJA MELALUICAREER PLATEAU (STUDI PADA SEKRETARIAT DAERAH KABUPATEN PATI) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimstoexamineandanalyzethe influence oforganizational climateandempowermenton thejob satisfaction through career plateau.Analysistoolused ismultiple regression, as fortesting the hypothesisusinga t test. Data collectionthroughquestionnairestomeasureusingLikertscaleof 7 (seven) alternativeanswers. Object of researchis employees at Sekretariat Daerah in Pati regency. Number of samplesin this study were111respondents. Samplingtechniqueusing thepurposive sampling. The results showed that(1)Organizational climatehave a negative and significant impact oncareer plateau, (2)Empowermenthave a negative and significantimpact oncareer plateau, (3)Organizational climatehave a positive and significant impact onjob satisfaction, (4)Empowerment have a positive and significantimpact onjob satisfaction, (5 ) Career plateauhave not effecton job satisfaction, (9)career plateau does not mediatetheeffect oforganizational climate on job satisfaction (10)career plateau does notmediate theeffect ofempowermenton job satisfaction. Keywords: Organizational Climate, Empowerment, Career Plateau and job satisfaction